Peran Kreativitas Guru dalam Meningkatkan Pengelolaan Kelas pada Pembelajaran Akidah Akhlak di MTs Yapika Kabupaten Kebumen - Khusnurrijal Khusnurrijal; Ali Mu’tafi; Hidayatu Munawaroh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to: 1) Find out how the teacher's strategy in classroom management in learning moral beliefs at MTs of the al istiqomah karya education foundation for Kebumen regency. 2) To find out how the Role of Teacher Creativity in Improving Classroom Management in Moral Faith Learning at MTs of the Al Istiqomah Karya Guna Education Foundation, Kebumen Regency. 3) To find out the supporting and inhibiting factors of Teacher Creativity in Classroom Management in Moral Faith Learning at MTs of the Al Istiqomah Karya Education Foundation in Kebumen Regency. This research uses a qualitative approach where the type of research is field research. The data collection technique uses observation, interview, and documentation methods related to the role of teacher creativity in improving classroom management in learning moral beliefs. The analysis techniques used are data reduction, data presentation and conclusion drawn. The results of the study showed that: 1) Teachers' strategies in classroom management in learning moral beliefs at MTs Al Istiqomah Karya Guna Education Foundation, Kebumen Regency. This includes setting up students' sitting positions every week, forming discussion groups, using learning media such as laptops and projectors, and providing constructive feedback. In addition, there are positive habits such as reading Asmaul Husna before learning begins to create a conducive classroom atmosphere. 2) The role of teacher creativity in improving classroom management in learning moral beliefs at MTs Al Istiqomah Karya Guna Education Foundation, Kebumen Regency. Teachers apply several approaches, such as taking turns seating each week, forming discussion groups, using learning media such as laptops and projectors, and providing constructive feedback. In addition, the habit of reading Asmaul Husna before the lesson starts is also carried out to foster discipline and a religious atmosphere in the classroom. Madrasah heads fully support this strategy by providing training for teachers, including training in the use of digital platforms and learning applications. 3) Supporting and Inhibiting Factors for Teacher Creativity in Classroom Management in Learning Moral Beliefs at MTs Al Istiqomah Karya Guna Education Foundation, Kebumen Regency. 1) Inhibiting factors from teachers. Heavy workloads such as teaching followed by extra-curricular teaching, superior classes or competition classes and other tasks at school that must be completed. 2) Student factors. a) Varying levels of student participation are sometimes an obstacle. Not all students are actively interacting, so it was difficult for me to create a dynamic and creative classroom atmosphere. This makes me have to continue to look for ways to make students more motivated and involved in the learning process. b) Students are difficult to manage or not communicative in the teaching and learning process.